Effects of selected soil and water conservation technologies onnutrient losses and maize yields in the central highlands of Kenya - Okeyo, A.I.; Mucheru-Muna, M.; Mugwe, Jayne; Ngetich, F.K.; Mugendi, Daniel N.; Diels, J.; Shisanyaaa, C.A. (Elsevier, 2014)
tMitigating nutrient loss is a prerequisite of sustainable agriculture in the tropics. We evaluated threesoil and water conservation technologies (mulching, minimum tillage and tied ridging) for two croppingseasons (long rains 2011, short rains 2011) at two sites in the central highlands of Kenya. The objectiveswere: to determine effects of the technologies on runoff, sediment yield and nutrient loads in sediment,and to assess influence of the technologies on maize yields. Experimental design was a randomizedcomplete block with 3 treatments replicated thrice. At the beginning of experiment, soil was sampledat 0–15 cm depth and analyzed for pH, N, P, K, C, Ca and Mg. Mulch was applied at a rate of 5 t ha−1.Runoff was sampled, sediments extracted by drying in oven at 105◦C, and analyzed for NPK and C loads.Data were subjected to analysis of variance using SAS 9.1.3 and means separated using Fishers’ LSD at5% level of significance. Results showed reduced nutrient losses with the technologies. In Meru South,sediment yield was reduced by 41 and 7% during long rains 2011 (p = 0.03), and by 71 and 68% duringshort rains 2011 (p = 0.01) under mulching and minimum tillage, respectively. Runoff and maize yieldswere positively influenced by mulching. In Mbeere South, sediment yield was lower under soil and waterconservation technologies. Runoff was reduced by 52 and 49% during long rains 2011 and by 51 and30% during short rains 2011 under tied ridging and mulching respectively, compared with control. Totalcrop failure occurred during long rains 2011 due to erratic rains. During short rains 2011 tied ridging andmulching increased maize yield by 94 and 75%, respectively, compared with control. This study highlightsthe importance of analyzing soil and water conservation technologies within rain-fed farming systemsperspective in response to declining food production and supports a focus on tied ridging and mulching
Keywords: Runoff; Food security; Rain-fed farming